WAVE PROPAGATION AND RESIDUAL CURRENT OF TIDE IN MAYALIBIT BAY: 2D HYDRODYNAMICS MODEL OF TIDE - Asep Sandra Budiman; Alan F. Koropitan; I Wayan Nurjaya (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Study on tidal waves and residual currents in Mayalibit Bay was conducted by constructing the 2D numerical hydrodynamics to find the characteristics of tide and residual currents inside the Bay. The 2D hydrodynamic equations with non-linier terms were solved by finite difference methods explicitly. M2 and K1 wave propagations were observed and analyzed at 25 observation points. M2 and K1 residual currents were obtained and described spatially. Simulation results of tidal currents were validated with field measurements. The validation result showed that the tidal currents between the model results and field measurements were quite fit. Generally, simulation results showed the significant differences between the tide inside and outside the Bay. This was strongly explained by the simulation results of M2 and K1 wave propagations. The M2 and K1 amplitudes were 10 times lower inside than outside the Bay with the phase lags of about 180°(M2) and 160°(K1). This result indicated that the tide inside and outside the Bay were in the opposite conditions. The tide had an ebb inside while the flood was outside and vice versa. M2 residual currents was flowed into the Bay uniformly, while K1 residual currents flowed out to the open sea in the Northern part and it flowed into the Bay in the Southern part of the Bay. Eventually, both of them converged in the middle of the Bay. Keywords: tide, tide-induced residual current, numerical method